2014
DOI: 10.4172/2167-0870.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Signaling Intrinsic to Sinoatrial Node Pacemaker Cells Affects Heart Rate Variability during Cardiac Disease

Abstract: The normal heart beat intervals are neither strictly stationary nor completely random, and continuously shift from one period to another. Decoding the ECG identifies this “hidden” information that imparts inherent complexity to the heart-beating interval time series. Loss of this complexity in cardiovascular disease is manifested as a reduction in heart rate variability (HRV) and this reduction correlates with an increase in both morbidity and mortality. Because HRV measurements are noninvasive and easy to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 84 publications
0
9
0
2
Order By: Relevance
“…Thus, the counterintuitive increase in HF in the elderly seems to be the result but not the cause of increased HRF. Several mechanisms can be considered for the genesis of HRF [5], which include sinus node exit block, subtle atrial bigeminy originating near or within the sinoatrial (SA) node, modulated SA node parasystole caused by multiple interacting pacemaker sites in the SA node [16], and modulated periodicity of pacemaker clock in the SA node [17,18]. Thus, increased HRF may be a marker reflecting the age-related degeneration or pathologic impairment of the SA-node-atrial network for cardiac pacemaker function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the counterintuitive increase in HF in the elderly seems to be the result but not the cause of increased HRF. Several mechanisms can be considered for the genesis of HRF [5], which include sinus node exit block, subtle atrial bigeminy originating near or within the sinoatrial (SA) node, modulated SA node parasystole caused by multiple interacting pacemaker sites in the SA node [16], and modulated periodicity of pacemaker clock in the SA node [17,18]. Thus, increased HRF may be a marker reflecting the age-related degeneration or pathologic impairment of the SA-node-atrial network for cardiac pacemaker function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RR power spectral analysis shows different spectral pattern according the class impairment and the related therapy. In the first two NYHA classes, the LF spectral component tend to increase (Guzzetti et al, 1995; Yaniv et al, 2014) whereas the most advanced stages are usually associated to a reduction of LF spectral power (Mortara et al, 1994; Guzzetti et al, 1995; Piccirillo et al, 2006, 2009b; Yaniv et al, 2014). The latter changes are also usually observed as quite physiological aging-related changes (Piccirillo et al, 1995, 1998) our sample with symptomatic AS showed a low short period heart rate variability and, consequently LF, in normalize and absolute power, but the patients were still able to increase LF during mental stress; probably this ability could be impaired in comparison with normal age-matched subjects (Piccirillo et al, 1995, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, studies that have analyzed the nonlinear dynamics and the complexity of HRV using short-term RR time series in MetS are scarce. Nevertheless, collectively, the increase in the different measures of entropy found in our study indicates low predictability of cardiac fluctuations and higher randomness and complexity in cardiac activity, which other researchers have related to pathological states such as myocardial infarction, arrhythmias, sinus sick syndrome, or mutations in intracellular Ca 2+ or surface membrane ion channel proteins [27,28].…”
Section: Discussionmentioning
confidence: 54%